Intercultural Communication in Mohsin Hamid’s The Reluctant Fundamentalist - Dhobi, Saleem (Cognition, 2022)
This paper analyzes Mohsin Hamid’s The Reluctant Fundamentalist that demonstrates Changez's intercultural relations with non-Muslim characters such as Erica, her father, his co-workers at Underwood Samson. The non-Muslim employees at Underwood Samson suspect Changez because of his beard as the American society has a mindset of beard. Erica‒Changez's beloved, and her father stereotype Changez based on his dress and beard. The beard reminds Americans of the 9/11 perpetrators. Their suspicion leads to detachment between Changez and non-Muslim characters in the aftermath. I employ John W. Berry's models of acculturation‒assimilation, separation, integration, and marginalization‒to analyze the intercultural communication. Integration as the most appropriate model of acculturation is the finding as the approach allows minorities to adapt to the dominant culture by retaining their native culture. The article refutes assimilation as a model of acculturation since it seeks the minority groups to adapt to mainstream culture by forgetting their culture of origin. Although Muslim protagonists struggle to integrate, they fail because of racial supremacy and religious extremism. The intercultural communication can be eased through reconciliation and coming together between minority Muslims and mainstream Americans.